Media Use and Perceived Academic Performance of Students in Public Universities in Osun State - Olumuyiwa Emmanuel Ojo; Tolulope Elizabeth Adenekan (International Journal of Media and Communication Research (IJMCR), 2023)
This study investigated media use and perceived academic performance of students in public universities in Osun State. A cross-sectional survey research design was adopted. The population consists of 38,385 students of public institutions with a sample size of 381 students determined through the Raosoft sample size determinant. Multi-stage random sampling technique was used to select students in the selected institutions in the state. A validated questionnaire was used to collect data. The data collected was analyzed using descriptive and inferential statistics. A reliability coefficient value for each variable in this study was recorded as follows; Media Use (MU) = 0.73; Perceived Academic Performance (PAP) = 0.81. Findings revealed that MU had a significant influence on the measures of PAP; self efficacy R2 = 0.124, F(1,343)= 39.753, p= 0.000, Learning Behaviour R2 = 0.104, F(1,343)= 39.753, p= 0.000. This study concluded that MU significantly influences PAP. The study recommended that students are to employ the right use of media as it will improve and aid their academic goals at all times.